(untitled) (Harmoni, 2024)
Abstract In Indonesia, religious moderation is crucial for it promotes tolerance and prevents the growth of extreme ideas, especially among the younger population. Despite its significance, there is a lack of study on students’ comprehension of religious moderation in areas like West Java, where intolerance is more prevalent and leaves a void in discussing educational tactics to raise awareness. This study aimed to assess how West Javan students perceive religious moderation and investigate methods for improving their knowledge and utilization of its tenets. The study employed a descriptive quantitative approach; data were gathered from 1,200 students actively involved in campus organizations at five West Javan universities. Questions about national identity, religious behaviors, and religious moderation were included in surveys disseminated using Google Forms. Clustering techniques were used to group student response patterns, and descriptive statistics, such as mean analysis, were used to evaluate general tendencies. The results highlighted the necessity for focused interventions, showing that while 43% of students lack adequate understanding, 57% of students comprehend religious moderation. There are, however, still gaps in addressing misunderstandings and extremism susceptibility despite the broad acceptance of Pancasila as a unifying concept and the general support for diversity and tolerance. These findings underscored the need for specialized educational programs that enhance students’ ability to foster tolerance and unity while highlighting students’ potential as agents of inclusion and harmony. Future studies should therefore concentrate on evaluating the success of these initiatives, comparing different geographical areas, and investigating how social media affects students’ attitudes toward religious moderation.